2012
DOI: 10.1371/journal.pone.0050358
|View full text |Cite
|
Sign up to set email alerts
|

Past Climate Change and Plant Evolution in Western North America: A Case Study in Rosaceae

Abstract: Species in the ivesioid clade of Potentilla (Rosaceae) are endemic to western North America, an area that underwent widespread aridification during the global temperature decrease following the Mid-Miocene Climatic Optimum. Several morphological features interpreted as adaptations to drought are found in the clade, and many species occupy extremely dry habitats. Recent phylogenetic analyses have shown that the sister group of this clade is Potentilla section Rivales, a group with distinct moist habitat prefere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
57
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 46 publications
(59 reference statements)
3
57
0
Order By: Relevance
“…Moreover, Asia and America also experienced an analogous arid period (Guo et al, 2002; Minnich, 2007; Graham, 2010). The extensive aridity can have promoted the diversification of some groups inhabiting in dry regions, such as Bursera (De-Nova et al, 2012) and the ivesioids of Potentilla (Töpel et al, 2012). De-Nova et al (2012) postulated that Bursera diversification during the Miocene might be related to the expansion of Mesoamerican seasonally dry tropical forests.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Asia and America also experienced an analogous arid period (Guo et al, 2002; Minnich, 2007; Graham, 2010). The extensive aridity can have promoted the diversification of some groups inhabiting in dry regions, such as Bursera (De-Nova et al, 2012) and the ivesioids of Potentilla (Töpel et al, 2012). De-Nova et al (2012) postulated that Bursera diversification during the Miocene might be related to the expansion of Mesoamerican seasonally dry tropical forests.…”
Section: Discussionmentioning
confidence: 99%
“…Other xeric-adapted woody taxa primarily associated with the CA-FP that molecular data indicate as having diverged from their nearest relatives in the Paleogene include Adenostoma (Rosaceae; Töpel et al 2012), Cneoridium (sister to Old World Haplophyllum, Rutaceae; Salvo et al 2010), Malosma (Anacardiaceae; Yi et al 2004), and Aesculus californica (Sapindaceae; Harris et al 2009). Molecular evidence for mesic-adapted, woody CA-FP endemic angiosperms of similar antiquity is relatively limited, e.g., Cornus sessilis (Cornaceae; Xiang et al 2008).…”
Section: Wwwannualreviewsorg • Origins Of Californian Plant Diversimentioning
confidence: 99%
“…Growing appreciation for the importance of ecology in understanding evolutionary change and recent evidence indicating evolutionary decoupling of niche parameters warrants more attention to resolving the history of ecological factors in a phylogenetic context as well (e.g., Emery et al 2012, Töpel et al 2012, Arrigo et al 2013, Anacker & Strauss 2014, in part to characterize likely future responses of lineages to environmental change. Field-based descriptive and experimental work is invaluable to these goals and, although often difficult and unavoidably slow, continues to be the source of some of the most important contributions to evolutionary understanding of the California flora (e.g., Ramsey et al 2003, Angert & Schemske 2005, Lowry et al 2008.…”
Section: Wwwannualreviewsorg • Origins Of Californian Plant Diversimentioning
confidence: 99%
“…Furthermore, Zhu et al (2013) used MAXENT modeling to project potential distributions of Spartina alterniflora on a global scale, based on the transferability of ENM predictions between native and invasive ranges. Climatic niche conservatism is the key assumption for the evaluation of the impact of climate change on distributions of invasive plant species (Petitpierre et al, 2012;Wiens and Graham, 2005;Töpel et al, 2012;Corlett and Westcott, 2013). Previous studies reported climatic factors to be an important driving force behind plant invasion into nonnative regions, because invasive plant species typically spread into areas with climatic conditions, similar to their native habitat; this is referred to as climatic niche conservatism (Petitpierre et al, 2012;Corlett and Westcott, 2013;Donoghue and Edwards, 2014).…”
Section: Introductionmentioning
confidence: 99%